Study on the mutagenicity and antimutagenicity of a natural food colour (annatto) in mouse bone marrow cells - Alves de Lima, R. O. [UNESP]; Azevedo, L.; Ribeiro, Lúcia Regina [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier, 2003)
Most manufactured foods contain chemicals added as a deliberate part of the manufacturing process. The aims of the present study were to evaluate the mutagenicity and antimutagenicity of annatto, a natural pigment extracted from the Bixa orellana L. and widely used as a colorant in foods. The micronucleus test was performed in bone marrow cells from Swiss male mice treated with one of the three concentrations of annatto (1330, 5330 and 10,670 ppm), incorporated into the diet. The animals were fed with the diets for 7 days and sacrificed 24 h after the last treatment. For the evaluation of the antimutagenic potential of annatto, at day 7, the animals received an intraperitoneal injection of cyclophosphamide (50 mg/kg body weight). Under the concentrations tested annatto did not present mutagenic or antimutagenic activities on the mice bone marrow cells. However, an increased frequency of micronucleated cells was observed when the highest concentration (10,670 ppm) was administered simultaneously with cyclophosphamide. In conclusion, the data indicate that annatto colour, for the conditions used, is neither mutagenic nor an inhibitor of induced mutations, although it should be used carefully since high doses may increase the effect of a mutagen. © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: Annatto; Antimutagenicity; Bixa orellana L.; Micronucleus; Mutagenicity; Natural food colours; annato; antimutagenic agent; bixa orellana extract; cyclophosphamide; food dye; mutagenic agent; plant extract; unclassified drug; animal cell; animal experiment; animal food; animal model; bixa orellana; bone marrow cell; controlled study; diet; male; micronucleus test; mouse; mutagenicity; mutation; nonhuman; plant; Administration, Oral; Animals; Antimutagenic Agents; Bixaceae; Bone Marrow Cells; Carotenoids; Cyclophosphamide; Diet; Dose-Response Relationship, Drug; Drug Synergism; Food Coloring Agents; Injections, Intraperitoneal; Male; Mice; Micronucleus Tests; Mutagens; Plant Extracts; Animalia; Bixa orellana